Equipe editorial (Revista Estética e Semiótica, 2024)
EQUIPE EDITORIALFundadoresDr. Flávio René Kothe, Universidade de Brasília – Brasília, BrasilDr. Júlio César Brasil, Secretaria de Estado de Educação do Distrito Federal;Conselho EditorialDr. Flávio René Kothe, Universidade de Brasília – Brasília, BrasilDra. Aline Stefania Zim, CEUB – Brasília, BrasilDra. Carolina da Rocha Lima Borges - UCB – Brasília, BrasilDr. Fernando Fuão, Faculdade de Arquitetura da UFRGS – Porto AlegreEditoria ExecutivaBárbara TavaresOrganização do DossiêDra. Aline ZimDra. Carolina da Rocha Lima BorgesDr. Fernando FuãoDr. Flávio René KotheLaura FrossardDaniel Gutenberg Eloi AnchietaComitê CientíficoDr. Ernildo Stein, Universidade Federal do Rio Grande do Sul, Porto Alegre, BrasilDr. Flávio R. Kothe, Universidade de Brasília, Brasília, BrasilDr. Sergio Rizo, Universidade de Brasília – Brasília, BrasilDr. Fernando Freitas Fuão, Universidade Federal do Rio Grande do Sul, Porto Alegre, BrasilDr. Guillermo De Santis, Universidad Nacional de Córdoba – ArgentinaDra. Carla Milani Damião, Universidade Federal de Goiás – Goiânia, BrasilDr. Manuel Curado – Universidade do Minho, PortugalDr. Marcos Carmignani, Universidad Nacional de Córdoba – ArgentinaDr. Marcos Carvalho Lopes, Universidade da Integração Internacional da Lusofonia Afro-brasileira – Redenção, Bahia, BrasilDr. Pedro Russi, Universidade de Brasília – Brasília, BrasilDr. Walter R. Menon Junior, Universidade Federal do Paraná – Curitiba, BrasilDiagramaçãoBárbara TavaresComitê de Redação do DossiêDra. Aline Stefânia ZimEndereço PostalFaculdade de Arquitetura e Urbanismo – FAU Universidade de Brasília – UnBInstituto Central de Ciências Ala Norte – ICC Norte – Gleba ACampus Universitário Darcy Ribeiro – Asa NorteBrasília – Distrito Federal70904-970